Medicinal Plants and their Uses in Begnas-Rupa Lake Area Pokhara, Nepal - Dwa, Om Prasad (Janapriya Journal of Interdisciplinary Studies, 2021)
Medicinal plants contain important phytochemicals and can be used for therapeutic functions. These plants were used and inherited to the people of Nepal from generations. Such plants have been used for health care by many people in rural area and deep rooted in villages of Nepal. Therefore, these plants are valuable assets of natural vegetation.